Analisis Lalu Lintas pada Ruas Jalan Lingkar Sicincin-Lubuk Alung Kab.Padang Pariaman untuk Disain Perkerasan - Dwina Archenita - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
Traffic is an important part of road pavement design in addition to subgrade strength. This is because traffic is a burden for the road and is very decisive in the thick planning of each layer of pavement. Thus the calculation of the traffic load should have been carried out before carrying out the design of the pavement. The Sicincin - Lubuk Alung ring road section located in Kab.Padang Pariaman is one of the road sections designed with pavement design. Therefore, a traffic survey was carried out on the road section. Traffic surveys are carried out for three days, two days on weekdays and one day on holidays. Every day the survey time is divided into three times, morning, afternoon and evening at rush hour. The survey in the morning takes place at 07:15 - 08:15 and 08:15 - 09:15 while in the afternoon it takes place at 13:00 - 14:00 and 14:00 - 15:00. Furthermore, for the afternoon survey, it will be held at 16:00 - 17:00 and 17:00 - 18:00. After processing the data, in each survey period the LHR value is obtained for both directions. The LHR value used for pavement design is the largest LHR value of all LHR values obtained.